ESCOLAS E FAXINAIS: REGIÕES DE SABERES, LUGARES DE MEMÓRIA (1980- 2014) - Galvão, Milene Aparecida Padilha (2015)
The study about faxinal’s in the South Central Region of Paraná state has enlarged ground among historians, so that there are new things to investigate. The faxinal’s system is characterized by a rich and natural culture. Property used in common, the division in planting and building domains, preservation of springs of water, the boundaries between the lands bounded by kill donkeys and or gates, the location basically in the region of Araucaria forests in southeastern Paraná are its main features. The faxinalense’s traditional knowledge are in frequent contact with other institutions such with formal education, which sets up a new plot, a new story. This is the story that we propose to understand and counting. In this thesis, we seek to understand how happen relations between faxinal’s and school in that it starts faxinalense’s activities in space and in some cases, cut up the place. This is not to investigate the education on the subject of teaching methods employed; the teaching used in the classroom or, much less, write the history of education in faxinais. It is, rather, to write the history of traditional peoples from the relationships established between the cultures of faxinalenses people has and school. From the selected temporal and spatial area - the municipalities of Irati, Rebouças and Rio Azul in the period 1980-2014, we made data collection, based on the portal INEP. Later, they began the research field, in order to locate the multigraded schools - 'small schools' - communities identified as faxinais in selected municipalities. Through the portal, we obtained data with which we can fabricate tables and graphs about the situation of education and schools in rural areas and with the location of schools in faxinais. Such schools were photographed and marked by the G.P.S. system. Students (and ex.) Teachers (and ex.) In the provided interviews describing the relationship of small schools with faxinal, its importance, the links that have been established, the memories and memories of that period. Our principal sources, besides the data set with tables and graphics are also photographs and interviews - key elements to understand the school and faxinais, which came to be regarded by us as regions to know. Said small schools as places of memory.